Worsening anatomic outcomes following aflibercept for neovascular age-related macular degeneration in eyes previously well controlled with ranibizumab [Corrigendum] - Nudleman E (Dove Medical Press, 2017)
Nudleman E, Wolfe JD, Woodward MA, Yonekawa Y, Williams GA, Hassan TS. Clinical Ophthalmology. 2016;10: 1053–1057.A units error was published on page 1055, column 2, as “3.1%”; the correct units are “μm” (3.1 μm).Read the original article.